Ultrasound-assisted extraction of flaxseed oil using immobilized enzymes - Long, Jing-jing; Fu, Yu-jie; Zu, Yuan-gang; Li, Ji; Wang, Wei; Gu, Cheng-bo; Luo, Meng (Bioresource technology, 2011)
► We set up an effective and clean way to extract flaxseed oil. ► Aqueous enzymatic process assisted by ultrasound extraction method was optimized. ► Kinetic parameters of the free and immobilized enzymes were studied. ► Oil shows good quality. An aqueous enzymatic process assisted by ultrasound extraction (AEP-UE) was applied to the extraction of oil from flaxseed (Linum usitatissimum L.). The highest oil recovery of 68.1% was obtained when ground flaxseed was incubated with 130U/g of cellulase, pectinase, and hemicellulase for 12h, at 45°C and pH 5.0. The IC50 values of oil obtained by AEP-UE and organic solvent extraction (OSE), as measured by DPPH scavenging activity essay, were 2.27mg/mL and 3.31mg/mL. The AEP-UE-derived oil had a 1.5% higher content of unsaturated fatty acids than the OSE-derived oil. AEP-UE is therefore a promising environmentally friendly method for large-scale preparation of flaxseed oil.